Applying theories of learning styles in e-learning with social networking tools - Miranda, Joanna Claire * (2012)
The main objective of this paper is to provide a bridging solution to adjustment problems of students migrating from secondary school system into college/university environment. It proposes an extended E-Learning through the use of existing varieties of online teaching modes. It propagates the extended E-Learning for the first semester modules that may be extended to a second semester to address team adjustment problems. This paper seeks to show how students can be made to work together in virtual groups before they meet in person. By being in a virtual team prior to physically being present in the university/college, it is proposed that this will reduce the teething problems of group/team work, a necessity in a college learning environment. The additional benefit to colleges/universities in using the recommended extended E-Learning method as an entry mode will be in the reduction in cases of students entering into the country with student visas for vice activities. Data was collected from first year foreign students in a private university in Malaysia to identify the link if any between students of a country to learning style and if the gender had any moderating effects. The findings on this batch of students showed that students from a country do not necessarily have the same learning style and furthermore that gender had no impact on their learning style. This allows for an implementation of study system based on Learning Style without having to consider the country of origin of the students. This study does not intend to negate the results of previous studies linking learning styles to country of origin. However, it shows that in a college environment and specifically in a module or subject the numbers of students from a same country will not be substantial to substantiate the past studies. This study was done in one Applying Theories of Learning Styles in E-Learning with Social Networking Tools private higher educational institute only due to limitation in human resource and finance. The importance of this study is to promote the idea of embracing the relevant technologies to enhance the higher education’s social and teaching methodology while ensuring students have a positive learning experience. This paper builds on the existing learning styles theories specifically Kolb’s Learning Styles Inventory.